Does Retirement Change What Individuals Value in Life? Results From a 3-Year Panel Study. (28th January 2022) - Grünwald, Olga; Damman, Marleen; Henkens, Kène
Abstract: Objectives: In previous research on retirement, what individuals value in life is often assumed to remain stable after the transition into retirement. However, retirement exposes individuals to new social settings and might thus prompt them to reevaluate their life orientations. Quantitative empirical knowledge about this process is limited, though. This study examines the impact of retirement on changes in the perceived importance of self-development, social status, societal contribution, and generativity in older adults' lives. We draw on the life-course framework to develop hypotheses about which life orientations are more likely to change after retirement and how. Methods: We analyzed data collected in 2015 and 2018 among 5, 034 Dutch individuals aged 60–65 and employed at baseline. Around half had fully retired at follow-up (either voluntarily or involuntarily), and 10% worked after retirement. Results: Conditional change models reveal that voluntary full retirement was linked to statistically significant—but (very) small—decreases in the importance of self-development, social status, societal contribution, and generativity compared to continuous career work. Differences in changes of life orientations between retirement processes (i.e., postretirement work, involuntary full retirement) were also small. Discussion: The findings point to relatively high levels of continuity during the transition from career employment to retirement, given the small effect sizes observed. The notion that after retirement, individuals will reevaluate what they value in life—as expected in light of the exposure-based mechanism from the life-course literature—seems to be less pronounced than initially expected.